Foreign business in China and opportunities for technological innovation and sustainable economics - Visvizi, Anna 1976-; Lytras, Miltiadis D. 1973-; Zhang, Xi 1982 December 28- (IGI Global, 2019)
"This book examines international business and innovation management in China and shows how new, advanced, international business and innovation models and adoptive strategies can expand the sustainability frontiers for China"--